Methyl jasmonate stimulates growth and upregulates the expression of Phenylalanine Ammonia-Lyase (PAL) gene in Gynura pseudochina in vitro micropropagation - TITAH RIGEL ANJALANI; SALMA ARGYA RASMI; ANISA ESTI RAHAYU; MUHAMMAD RIFQI NUR RAMADHANI; MAY FIATUS SHOLIHAH; IRA PUSPANINGTYAS; IRO DATUS SOLEHA; SEPTI ANITA SARI; MAULIDIA RAHMAWATI; NASORI NASORI; NURUL JADID (Society for Indonesian Biodiversity, 2024)
Abstract. Anjalani TR, Rasmi SA, Rahayu AE, Ramadhani MRN, Sholihah MF, Puspaningtyas I, Soleha ID, Sari SA, Rahmawati M, Nasori N, Jadid N. 2024. Methyl jasmonate stimulates growth and upregulates the expression of Phenylalanine Ammonia-Lyase (PAL) gene in Gynura pseudochina in vitro micropropagation. Biodiversitas 25: 1955-1964. The use of medicinal plants as primary resources for traditional medicine is rising. Gynura pseudochina (L) DC. is a well-recognized traditional medicinal plant from Southeast Asia. It is rich in bioactive compounds like flavonoids, alkaloids, saponins, and tannins. Various techniques and methods have been developed to ensure plant quality and enhance phytomedicines' production, one of which involves plant in vitro culture. Elicitor-based in vitro culture, particularly using Methyl Jasmonate (MeJA), has been shown to boost the production of secondary metabolites in plants through the overexpression of Phenylalanine Ammonia-Lyase (PAL) genes, known to play a role in the excessive production of flavonoid compounds. This research aims to investigate the impact of MeJA on the growth and PAL gene expression in G. pseudochina in vitro culture. Several MeJA concentrations of MeJA (0, 75, 150, and 300 µM) were tested. Our findings revealed that the application of MeJA to G. pseudochina in vitro had a noticeable impact on callogenesis and organogenesis. The optimal condition for callogenesis was achieved with MeJA at a concentration of 150 µM. On the other hand, the highest frequency of root induction was observed at 75 µM of MeJA treatment, while the highest shoot frequency occurred at 150 µM of MeJA. Interestingly, the plant height, fresh weight, leaf, and shoot numbers were significantly affected after treatment with 150 µM of MeJA. Additionally, 75 µM of MeJA was found to promote optimal root growth compared to other MeJA treatments. Finally, 150 µM of MeJA treatment resulted in higher expression of the PAL gene (1.29 folds) than the non-treated plants. Our findings suggested that MeJA influenced the G. pseudochina growth and potentially increased the production of flavonoid compounds in vitro.